2015
DOI: 10.1108/jwl-07-2013-0049
|View full text |Cite
|
Sign up to set email alerts
|

The role of natural abilities, intrinsic characteristics, and extrinsic conditions in air traffic controllers’ vocational development

Abstract: Purpose – The purpose of this paper is to apply the Developmental Model of Vocational Excellence (DMVE) in the domain of air traffic control and to describe the characteristics and predictors related to air traffic controllers’ (ATCO) vocational expertise and excellence. Based on DMVE, the study analyses the role of natural abilities (gifts), intrinsic characteristics (self-regulatory abilities) and extrinsic conditions (domain and non-domain specific factors) in ATCOs’ vocational development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…On the third level, lay critical and creative thinking skills, which lead to academic success (Kaufman et al 2008). The following layers compose individual's metacognitive skills; metacognitive skills are at the top of this hierarchy because it has been found that they can distinguish expertise from excellence (Pylvas, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the third level, lay critical and creative thinking skills, which lead to academic success (Kaufman et al 2008). The following layers compose individual's metacognitive skills; metacognitive skills are at the top of this hierarchy because it has been found that they can distinguish expertise from excellence (Pylvas, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Motivation assists learners to formulate decisions and promote decision-making accompanied by volitional processes, which guide the subsequent enactment of the decision. Moreover, self-reflection is congruent with intrapersonal skills, which correspond to one's need to form attribution interpretations for success or failure (Pylvas, 2015, Macnamara, 2016. Critical reflection on one's own experiences carries two important benefits for the individual; first, these self-reactions are under one's own control and strengthen one's tolerance of stress and commitment to the task, thus help the learner to identify the best coping strategies in a given situation and enhance his self-efficacy (Starks, 2014).…”
Section: Research Highlightsmentioning
confidence: 99%
See 2 more Smart Citations
“…The developmental model of vocational and professional excellence (DMVE) (Nokelainen, 2016;Pylväs, Nokelainen, & Roisko, 2015) is developed on the basis of the earlier empirical research on modeling of vocational expertise and excellence (Nokelainen, Stasz & James, 2013;Nokelainen, 2010;Ruohotie, Nokelainen, & Korpelainen, 2008;Tirri & Nokelainen, 2011;Nokelainen, Tirri, Campbell, & Walberg, 2007;Nokelainen & Ruohotie, 2002). The DMVE model is applied in this study to investigate the vocational skills competition participants', their co-workers' and their employers' perceptions of the natural abilities, intrinsic characteristics (self-regulation) and extrinsic conditions that influence the development of vocational expertise.…”
Section: Developmental Model Of Vocational and Professional Excellencementioning
confidence: 99%